2020
DOI: 10.1001/jama.2020.3138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preemptive Therapy vs Antiviral Prophylaxis on Cytomegalovirus Disease in Seronegative Liver Transplant Recipients With Seropositive Donors

Abstract: IMPORTANCE Despite the use of a cytomegalovirus (CMV) prevention strategy of antiviral prophylaxis for high-risk CMV-seronegative liver transplant recipients with seropositive donors, high rates of delayed-onset postprophylaxis CMV disease occur. An alternate approach, preemptive therapy (initiation of antiviral therapy for early asymptomatic CMV viremia detected by surveillance testing), has not previously been directly compared with antiviral prophylaxis in these patients.OBJECTIVE To compare preemptive ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
149
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(187 citation statements)
references
References 34 publications
7
149
2
Order By: Relevance
“…To account for the difference in time to infection following VGC prophylaxis among CMV risk cohorts, we considered a number of possibilities, including the role of CMV‐specific CMI in preventing CMV infection and disease following SOT 20‐22 . In a study of 95 CMV HR (D+R−) SOT recipients, evidence of CMV CMI following VGC prophylaxis was associated with protection from subsequent CMV infection in 92%‐100% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for the difference in time to infection following VGC prophylaxis among CMV risk cohorts, we considered a number of possibilities, including the role of CMV‐specific CMI in preventing CMV infection and disease following SOT 20‐22 . In a study of 95 CMV HR (D+R−) SOT recipients, evidence of CMV CMI following VGC prophylaxis was associated with protection from subsequent CMV infection in 92%‐100% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 To account for the difference in time to infection following VGC prophylaxis among CMV risk cohorts, we considered a number of possibilities, including the role of CMV-specific CMI in preventing CMV infection and disease following SOT. [20][21][22] In a study of 95…”
Section: Dnaemia and Disease Among Riskstratified Children In Tmentioning
confidence: 99%
“…Although there is no study comparing different intervals of CMV testing, studies evaluating preemptive approaches with frequent testing have shown non-inferiority to prophylaxis even in high-risk patients (D+/R−) [34][35][36]. (b) In patients with prophylaxis, testing can be reduced to monthly, followed by every 3 months (or in case of symptoms) for the first year.…”
Section: Conclusion CMV Diagnostic Strategiesmentioning
confidence: 99%
“…International practice guidelines for liver transplantation are only precise in the high-risk scenario (D+/R−), recommending pharmacological CMV prophylaxis for at least 3 months [5,25,37]. However, a recent study showed that an adequate monitoring and low threshold for treatment initiation, i.e., immediately upon detection of viremia, allows the application of a preemptive therapy approach also for high-risk patients [36]. The efficacy of preemptive therapy strongly correlates with a high frequency of DNA testing in order to detect the dynamics of DNA quantification before the patient becomes symptomatic.…”
Section: Preventive Strategies For CMV Infectionsmentioning
confidence: 99%
See 1 more Smart Citation